2019
DOI: 10.1590/1980-57642018dn13-030010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive abilities and physical activity in chronic kidney disease patients undergoing hemodialysis

Abstract: Hemodialysis (HD) is a common treatment for Chronic Kidney Disease (CKD). Objective: the objective of the present study was twofold. First, to assess the level of physical activity and cognitive function in hemodialysis (HD) patients and, second, to compare cognitive function of active and insufficiently active HD patients. Methods: the sample consisted of 84 HD patients. Data collection took place in two different Renal Replacement Therapy Units (RRTU) in Brazil. A sociodemographic and clinical structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
2
0
3
Order By: Relevance
“…Embora a relação entre a melhora da qualidade de vida e bom nível de atividade física já tenha sido descrita em outros estudos com pacientes em hemodiálise [5][6][7] , este estudo traz um diferencial de mostrar cientificamente este resultado com o equipamento pedômetro que é de fácil acesso aos serviços de hemodiálise em seu processo de avaliação e acompanhamento de seus pacientes. Algumas limitações do estudo podem ser destacadas, e entre elas a avaliação de único centro regional, o que pode diminuir o poder de generalização dos resultados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Embora a relação entre a melhora da qualidade de vida e bom nível de atividade física já tenha sido descrita em outros estudos com pacientes em hemodiálise [5][6][7] , este estudo traz um diferencial de mostrar cientificamente este resultado com o equipamento pedômetro que é de fácil acesso aos serviços de hemodiálise em seu processo de avaliação e acompanhamento de seus pacientes. Algumas limitações do estudo podem ser destacadas, e entre elas a avaliação de único centro regional, o que pode diminuir o poder de generalização dos resultados.…”
Section: Discussionunclassified
“…A atividade física é relatada como uma alternativa terapêutica não farmacológica e de baixo custo 5 além de beneficiar a função cardiorrespiratória, melhorar a qualidade de vida 6 e ser preditora de desfechos clínicos adversos em pacientes com doença renal 7 . Contudo, a maioria dos pacientes submetidos à hemodiálise apresentam baixos níveis de atividade física 8 .…”
Section: Introductionunclassified
“…The cross-sectional study by Fukushima et al (2019) compared physically active and inactive patients and revealed that the mean total score on the cognitive test was lower than recommended and that those on hd physically active obtained a significant score in the domain of verbal fluency. These results suggest that a higher physical activity level can contribute to a higher cognitive function score, being a potential therapeutic alternative.…”
Section: Palabras Clave: Insuficiencia Renal Crónica; Fenómenos Fisio...mentioning
confidence: 98%
“…A pilot RCT also suggested that exercise training had positive impact on stemming cognitive impairment (Mcadams‐Demarco et al, 2018). Overall, evidence examining the influence of exercise on cognitive function in this patient group is scarce (Fukushima et al, 2019). The effects of different exercise modalities, durations, frequencies and intensities of exercise on cognitive function remain unknown (Afsar et al, 2018; Manfredini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%